MATHEMATICAL MODELING OF EYE ACCOMMODATION PROCESS WITH ARTIFICIAL CRYSTAL - Troyanov , P. P.; Dashkevich , O. O.; Troyanov , D. P. (Problems of Informatization and Management, 2021)
A mathematical model of the known design of the accommodation lens of the eye is proposed and its dynamic and static characteristics are determined.